Method for calculating solubility product of water dispersible polyester in divalent metal ion solution and application
By calculating the solubility of water-dispersible polyester in the solution containing divalent metal ion, the aggregation and precipitation problems during the desizing process are solved, the quantitative evaluation of dissolution stability and the optimization of the desizing process are achieved, and the treatment efficiency and environmental protection performance are improved.
Patent Information
- Application Number
- CN202411634071.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art lacks effective quantitative means to deal with the aggregation and precipitation behavior of water-dispersible polyester in divalent metal ion solutions, resulting in limitations of polyester desizing process and wastewater treatment technology.
By measuring and calculating the solubility product (Ksp) of water-dispersible polyester in a solution containing divalent metal ion, combining the critical micelle concentration and critical polysalt concentration, the dissolution stability is accurately evaluated, and the adjustment of desizing process parameters is guided.
Quantitative evaluation of the dissolving stability of water-dispersible polyester is achieved, which reduces aggregation and precipitation during the desizing process, improves the desizing efficiency and fabric quality, and reduces the cost of wastewater treatment.
Smart Images

Figure CN119724377A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of textile chemistry and material science, and in particular to a solubility product calculation method of water-dispersible polyester in a divalent metal ion solution and an application thereof. Background Art
[0002] Water-dispersed polyester (WPET) has a molecular structure similar to that of polyester. It has excellent adhesion to polyester and is cheap. Therefore, water-dispersed polyester sizing is often used to treat polyester warp yarn. - ) has been introduced to make water-dispersible polyester have good dispersibility in water. In recent years, water-dispersible polyester has been used in the sizing of polyester / cotton blended yarn, pure polyester yarn and polyester filament warp yarn, and has achieved good sizing and weaving effects. However, in the actual desizing process of water-dispersible polyester (water-dispersible polyester) sizing, it is often observed that the water-dispersible polyester tends to aggregate and even precipitate due to the sulfonated monomer content of the water-dispersible polyester. Especially in high-hardness water, the already aggregated water-dispersible polyester adheres to the polyester fiber, which will seriously pollute the surface of the polyester fabric. Not only does it bring inconvenience to the subsequent processing of polyester fabrics, but also a large amount of water is required to clean the precipitates on the surface of the fabric, resulting in an increase in energy consumption and wastewater. Factories urgently need to consider proposing improvement measures to reduce the cost of treating wastewater, which requires considering the source and cause of precipitation and controlling it to a certain extent. At present, there is still a lack of effective quantitative means for the aggregation and precipitation behavior of water-dispersible polyester in such solutions, which limits the further improvement of polyester desizing process and wastewater treatment technology.
[0003] At present, the calculation methods of solubility product are mainly used in the dissolution system of small molecule electrolytes. These calculations can help understand the maximum solubility of compounds in solution and the precipitation conditions. However, for macromolecular polymers such as water-dispersible polyesters, due to their structural complexity and intermolecular interactions, which are significantly different from small molecule electrolytes, the existing solubility product theory is not directly applicable. Therefore, a simple and widely recognized method is needed to accurately calculate or predict the solubility of such polymer materials in different scenarios. Summary of the invention
[0004] The present invention aims at the problem that there is no method to accurately quantify the aggregation and precipitation behavior of water-dispersible polyester in a solution containing divalent metal ions during the desizing process of polyester fabrics. A method for calculating the solubility product of water-dispersible polyester in a solution containing divalent metal ions is constructed and applied in the desizing process of polyester fabrics and desizing wastewater treatment. The method realizes quantitative evaluation of the dissolution stability of water-dispersible polyester by accurately measuring and calculating the solubility product (Ksp) of water-dispersible polyester in a solution containing divalent metal ions.
[0005] The above method specifically comprises the following steps: (1) Preparing a water-dispersible polyester solution; (2) Determination of the critical micelle concentration [-SO3 - ] crit ; (3) Determination of the critical coagulation concentration [M] of divalent metal ions in water-dispersible polyester solutions 2+ ] crit ; (4) Calculate the solubility product Ksp and solubility S by formula (1) and formula (2); K sp= [ −SO 3 − ] crit 2 × [ M 2+ ] crit (1) (2).
[0006] Ksp is the solubility product, [-SO3 - ] Crit (unit mol / L) is the concentration of water-dispersible polyester that exists as a single molecule without aggregation, that is, the critical micelle concentration, [M 2+ ] crit (unit mol / L) is the concentration of a single divalent counterion or an unbound divalent counterion, that is, the minimum concentration of counterions required to cause precipitation of water-dispersible polyesters, which is the critical coagulation concentration. S is the solubility, which refers to the amount of solute that can be dissolved in a unit solvent, in mol / L.
[0007] Further, the water-dispersible polyester solution is prepared by the following method: adding water-dispersible polyester solid particles into deionized water, heating to 95° C., stirring at a speed of 300 rpm, and stirring for 30 min; Furthermore, the conductivity of the deionized water is in the range of 0-10 μS / cm.
[0008] If the solubility product of the sulfonic acid polymer salt in the water-dispersible polyester solution is calculated, it is necessary to know the critical micelle concentration of the water-dispersible polyester and the minimum concentration of counterions required to cause the precipitation of the water-dispersible polyester, that is, the critical coagulation concentration of the divalent metal ion. Among them, the critical micelle concentration is determined by the dynamic light scattering method. The light scattering intensity increases with the increase of the concentration of the water-dispersible polyester. When micelles are formed, the light scattering intensity suddenly increases, and the mutation point is the critical micelle concentration.
[0009] Furthermore, the critical micelle concentration was measured by the following method: a series of solutions of 0.005-0.500 g / L were prepared from a water-dispersible polyester stock solution with a concentration of 1.00 g / L. The light scattering intensity of the aqueous solution at different water-dispersible polyester concentrations was tested, and three tests were performed at each concentration and the average value was taken. The light scattering intensity (I)-water-dispersible polyester concentration (C) curve was plotted, and the water-dispersible polyester concentration corresponding to the light scattering intensity mutation point was found to be the critical micelle concentration.
[0010] Furthermore, the critical coagulation concentration (C crit ) is measured by the following method (the divalent metal ions include magnesium ions, calcium ions, ferrous ions, copper ions, etc.): The critical coagulation concentration of divalent metal ions in water-dispersible polyester solutions is measured by dynamic light scattering to determine the change in solution particle size. The critical coagulation concentration is the lowest counterion concentration that induces the aggregation of colloidal particles. Above this concentration, spontaneous aggregation will occur and the particle size will increase rapidly. The critical coagulation concentration is at the inflection point of the curve of solution particle size-divalent metal ion concentration.
[0011] The critical coagulation concentration was studied using a 5.00 g / L water-dispersible polyester solution. Different concentrations of divalent metal ions were added to the 5.00 g / L water-dispersible polyester solution, and the changes in the solution particle size with the divalent metal ion concentration were studied. The average particle size-metal ion curve of the solution was drawn, and the mutation point was the critical ion concentration corresponding to the water-dispersible polyester solution.
[0012] The present invention also provides an application of the above calculation method in the desizing process of polyester fabric and the treatment of desizing wastewater. By measuring or calculating the solubility product (Ksp) of water-dispersible polyester in divalent metal ion solutions of different concentrations, on the one hand, its solubility stability can be evaluated, thereby guiding the adjustment of desizing process parameters, reducing precipitation, and improving fabric processing efficiency and environmental performance; on the other hand, in the subsequent wastewater treatment, the flocculation treatment of water-dispersible polyester can be achieved in the most economical way, reducing the cost of subsequent wastewater treatment.
[0013] Beneficial effects of the present invention: (1) Quantitative evaluation of dissolution stability: This method can achieve quantitative evaluation of the dissolution stability of water-dispersible polyester by accurately measuring and calculating the solubility product (Ksp) of water-dispersible polyester in divalent metal ion solution. This helps to deeply understand the dissolution behavior of water-dispersible polyester under different water quality conditions and provides a scientific basis for the optimization of desizing process.
[0014] (2) Optimization of desizing process: Based on the predicted solubility product results, the adjustment of desizing process parameters, such as desizing temperature, time, and water hardness, can be guided, thereby effectively reducing the aggregation and precipitation of water-dispersible polyester during the desizing process and improving the desizing efficiency and fabric quality.
[0015] (3) Improving wastewater treatment efficiency: By reducing the precipitation of water-dispersible polyester during the desizing process, this method helps to reduce the pollutant content in the wastewater, reduce the burden of wastewater treatment, improve wastewater treatment efficiency, and reduce treatment costs. This is of great significance for achieving energy conservation, emission reduction and sustainable development in the textile industry.
[0016] (4) Promoting energy conservation and emission reduction: By optimizing the desizing process and wastewater treatment process, the method of the present invention helps to reduce the consumption of water resources and energy, reduce carbon emissions, and play a positive role in promoting the green transformation of the textile industry.
[0017] (5) Enhanced technological innovation capabilities: The invention fills the current technical gap in the quantitative evaluation of the solubility behavior of water-dispersible polyesters, provides new research ideas and methods for the field of textile chemistry and materials science, and helps promote technological innovation and development in this field. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a graph showing the test results of critical micelle concentration of three water-dispersible polyester slurries.
[0019] Figure 2 This is a graph showing the test results of the critical coagulation concentration of magnesium ions for three water-dispersible polyester slurries.
[0020] Figure 3 This is a graph showing the test results of the critical coagulation concentration of calcium ions for three water-dispersible polyester slurries.
[0021] Figure 4 The figure shows the flocculation results of three water-dispersible polyester slurries with the same concentration and different concentrations of typical divalent metal ions. DETAILED DESCRIPTION
[0022] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.
[0023] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.
[0024] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0025] In the present invention, the meaning of crit in formulas (1) and (2) is common knowledge in the art, and means "critical"; the unit mM represents the concentration unit mmol / L.
[0026] Example 1 1. Preparation of slurry solution Weigh a certain amount of water-dispersible polyester solid particles and add them to a beaker filled with an appropriate amount of deionized water (conductivity of 5.84uS / cm). Place the beaker on a heating device and heat it to 95°C. At the same time, turn on the stirrer and set the stirring speed to 300 rpm. Continue stirring for 30 minutes to ensure that the water-dispersible polyester is fully dissolved and evenly dispersed in the deionized water. After the solution cools to room temperature, dilute it with deionized water to the required different concentrations for subsequent testing.
[0027] The molecular weight information of the water-dispersible polyester slurry is shown in Table 1.
[0028] Table 1 Molecular weight information of water-dispersible polyesters WPET Samples <![CDATA[Weight-average molecular weight (M w , g / mol)]]> The ratio of sulfonated monomer to total monomer A <![CDATA[2.245×10 4 ]]> 14.2% B <![CDATA[2.276×10 4 ]]> 11.6% C <![CDATA[2.241×10 4 ]]> 9.1% 2. Calculation of solubility product Ksp and solubility S of calcium sulfonate and magnesium sulfonate in water-dispersible polyester solution 2.1 Determination of critical micelle concentration (CMC) of water-dispersible polyester by dynamic light scattering Using a water-dispersible polyester stock solution with a concentration of 1.00 g / L, a series of water-dispersible polyester solutions with a concentration range of 0.005~0.500 g / L were prepared by stepwise dilution. The water-dispersible polyester solutions of each concentration were placed in the sample cell of the dynamic light scattering instrument. The dynamic light scattering instrument was started to test and record the light scattering intensity of the solution at each concentration. Each concentration was tested three times and the average value was taken to improve the accuracy of the data. Based on the test data, a light scattering intensity-water-dispersible polyester concentration curve was drawn. Figure 1 The light scattering intensity suddenly increases at the mutation point shown in Table 2. The water-dispersible polyester concentration corresponding to this point is the critical micelle concentration (CMC). As shown in Table 2, it is the critical micelle concentration of different water-dispersible polyester molecular weights.
[0029] Table 2 Critical micelle concentration of different water-dispersible polyester molecular weights WPET Samples CMC (mol / L) A <![CDATA[7.528×10 -6 ]]> B <![CDATA[4.438×10 -6 ]]> C <![CDATA[3.347×10 -6 ]]> 2.2 Determination of critical calcium ion coagulation concentration (C) by dynamic light scattering crit-Ca ) Take 5.00 g / L water-dispersible polyester solution as the reference solution. Gradually add different concentrations of calcium ion (Ca²⁺) solution to the reference solution, stir thoroughly after each addition and use dynamic light scattering to test and record the average particle size of the solution after each addition of ions. Repeat the test three times for each ion concentration and take the average value. According to the test data, draw the curve of average particle size-calcium ion concentration of the solution. Figure 3 The inflection point of the curve shown in FIG. 1 is the critical calcium ion concentration (C crit-Ca ).
[0030] 2.3 Determination of critical coagulation concentration (C) of magnesium ions by dynamic light scattering crit-Mg ) Take 5.00 g / L of water-dispersible polyester solution as the reference solution. Gradually add different concentrations of magnesium ion (Mg²⁺) solution to the reference solution, stir thoroughly after each addition and use a dynamic light scattering instrument to test and record the average particle size of the solution after each addition of ions. Repeat the test three times for each ion concentration and take the average value. Based on the test data, draw a curve of the average particle size of the solution-magnesium ion concentration. Figure 2 The inflection point of the curve shown in FIG. 1 is the critical magnesium ion concentration (C crit-Mg ).
[0031] 2.4 Calculation of solubility product Ksp and solubility S According to the above steps, the critical micelle concentration (CMC) and critical coagulation concentration (C crit-Ca ) and critical coagulation concentration (C crit-Mg ), substituted into the calculation formula (1) of the solubility product (Ksp), the solubility product Ksp (WPET-Ca) of calcium sulfonate and the solubility product Ksp (WPET-Mg) of magnesium sulfonate in the water-dispersible polyester solution containing calcium ions are obtained. Substituting the obtained Ksp (WPET-Ca) into the formula (2) to obtain the solubility S (WPET-Ca) of calcium sulfonate in the water-dispersible polyester solution. Substituting the obtained Ksp (WPET-Mg) into the formula (2) to obtain the solubility S (WPET-Mg) of magnesium sulfonate in the water-dispersible polyester solution.
[0032] Table 3 Ksp and S of calcium sulfonate in three WPET solutions WPET Samples <![CDATA[C crit-Ca (mol / L)]]> Ksp(WPET-Ca) S(WPET-Ca) A <![CDATA[8.93×10 -4 ]]> <![CDATA[5.061×10 -14 ]]> <![CDATA[2.330×10 -5 ]]> B <![CDATA[7.76×10 -4 ]]> <![CDATA[1.453×10 -14 ]]> <![CDATA[1.537×10 -5 ]]> C <![CDATA[5.45×10 -4 ]]> <![CDATA[6.105×10 -15 ]]> <![CDATA[1.151×10 -5 ]]> In the calcium ion solution, the Ksp order of the three water-dispersible polyesters and sulfonate groups to form precipitates is Ksp(A)>Ksp(B)>Ksp(C), and the solubility S order is S(A)>S(B)>S(C), that is, compared with the water-dispersible polyester slurries B and C, the water-dispersible polyester slurry A is less likely to precipitate in the calcium ion solution, which is consistent with the actual dispersion effect of the three water-dispersible polyesters in the calcium ion solution.
[0033] Table 4 Ksp and S of magnesium sulfonate in three WPET solutions WPET Samples <![CDATA[C crit-Mg (mol / L)]]> Ksp(WPET-Mg) S(WPET-Mg) A <![CDATA[8.546×10 -3 ]]> <![CDATA[4.843×10 -13 ]]> <![CDATA[4.497×10 -5 ]]> B <![CDATA[7.729×10 -3 ]]> <![CDATA[1.522×10 -13 ]]> <![CDATA[3.363×10 -5 ]]> C <![CDATA[7.369×10 -3 ]]> <![CDATA[8.255×10 -14 ]]> <![CDATA[2.743×10 -5 ]]> In the solution containing magnesium ions, the Ksp order of the three water-dispersible polyesters and sulfonate precipitates is also Ksp(A)>Ksp(B)>Ksp(C), and the solubility S order is S(A)>S(B)>S(C), that is, compared with water-dispersible polyester slurries B and C, water-dispersible polyester slurry A is less likely to coagulate in the solution containing magnesium ions, which is consistent with the actual dispersion effect of the three water-dispersible polyesters in the solution containing calcium and magnesium ions. It is worth noting that the above examples also show that the coagulation ability of magnesium ions combined with water-dispersible polyester slurry is weaker than that of calcium ions, which also shows that when polyester fabrics are desized, less attention can be paid to magnesium ions than calcium ions; and when treating desizing wastewater, calcium salts should be used as much as possible for treatment.
[0034] The above embodiments describe in detail the structure, features and effects of the present invention. The above are only preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the scope covered by the specification, should be within the protection scope of the present invention.
Claims
1. A method for calculating the solubility product of a water-dispersible polyester in a divalent metal ion solution, characterized in that: The following steps are involved: (1) Preparing a water-dispersible polyester solution; (2) Determination of the critical micelle concentration [-SO3 - ] crit ; (3) Determination of the critical coagulation concentration [M] of divalent metal ions in water-dispersible polyester solutions 2+ ] crit ; (4) Calculate the solubility product Ksp and solubility S by formula (1) and formula (2); (1) (2)。 2. The method according to claim 1, characterized in that The method for preparing the water-dispersible polyester solution in step (1) is as follows: adding water-dispersible polyester solid particles into deionized water, heating to 95° C., stirring at a speed of 300 rpm, and stirring for 30 minutes.
3. The method according to claim 2, characterized in that The conductivity of the deionized water is in the range of 0-10 μS / cm.
4. The method according to claim 1, characterized in that The critical micelle concentration in step (2) is measured by the following method: preparing an aqueous solution of a water-dispersible polyester with a concentration of 0.005-0.500 g / L, testing the light scattering intensity of the solution at different concentrations, and the concentration corresponding to the mutation point of the light scattering intensity is the critical micelle concentration.
5. The method according to claim 1, characterized in that The critical coagulation concentration described in step (3) is measured by the following method: adding different concentrations of divalent metal ions to a 5.00 g / L water-dispersible polyester solution, measuring the change in the solution particle size with the concentration of the divalent metal ions, and the particle size mutation point is the critical coagulation concentration corresponding to the water-dispersible polyester solution.
6. The method according to claim 1, characterized in that The divalent metal ions include one of magnesium ions and calcium ions.
7. Use of the method according to claim 1 in the desizing process of polyester fabric and the treatment of desizing wastewater.